Effect of variation of TIG welding current on tensile strength and hardness of aluminium A-6061 - Azwinur Azwinur; Syukran Syukran (Politeknik Negeri Lhokseumawe, 2021)
Aluminium is a material that is now widely used for welding because this material has good mechanical properties, is corrosion resistant, is light in weight and can be recycled. The problem that occurs in aluminium welding is the presence of a passive layer or layer of Al2O3 oxide which has a high affinity for oxygen. This oxide layer is also an insulator which can inhibit the flow of current in welding. The amount of current in the welding process greatly affects the amount of heat input, weld concentration and arc stress. The purpose of this study was to determine changes in the mechanical properties of tensile strength and hardness of welded metal joints with variations in welding current on aluminium Al-6061 using the TIG welding process. The stages of the research method carried out were to carry out the TIG welding process on aluminium material joints with variations in currents of 120A, 140A and 160A. The filler rods used were AWS A5.10/ER-5356 and argon gas with a flow volume of 15 l/m. Furthermore, the results of the weld are tested for tensile and hardness to determine changes in the mechanical properties of the weld joint. The results show that the magnitude of the welding current affects the strength of the welding joint in terms of mechanical properties, especially the value of the tensile strength and hardness of the material when receiving loads and also affects the strain or elongation of a material. The highest tensile strength value is at a current strength of 160A of 9.83 Kgf/mm2, while the lowest tensile strength value is welding using a current strength of 120A with a value of 9.73 Kgf/mm2. The most ductile or ductile welded joints are welding using a current of 120A. While the highest hardness value was in the 160A weld metal area of 95.17 HRE and the lowest was in the HAZ area of 160A current of 41.17 HRE